Experimental Study of Reinforcing Broken Gangues by Colloid Cement Slurry - Xin Lyu; Ke Yang; Qiang Fu; Zhen Wei; Shuai Liu (Shock and Vibration)
Studies on jet grouting materials mainly focus on the aggregates in cement or the environment where they are maintained and rarely deal with the cohesiveness, reinforcement load-bearing characteristics, and surface spalling. In this study, cement slurries with different colloid contents were prepared to explore the characteristics and reinforcement effect of broken gangues. These were then subjected to mechanical testing to measure the strength and axial strain performance, and the failure modes and failure patterns were discussed. The results indicated that the colloid component has a significant strengthening effect on the early strength of the samples. As the age increased, the sample axial strain and elastic modulus of the colloid cement paste increased as the colloid component provides viscoelasticity when it resists deformation. The sample strength of cement paste decreases after the addition of broken gangue while the strength of class E samples increases significantly during each age. The cement paste sample showed penetrating splitting failure, the colloidal component effectively controlled the peeling of sample surface, and the failure mode after adding gangue was relatively complicated. The instability modes of the samples are divided into dispersed load-bearing instability and cumulative load-bearing instability, and the content of colloid components affects the failure mode of the samples. A colloid component proportion of 23.33% is the optimal choice, which has an obvious reinforcement effect on the broken gangue.